THU0400 CLINICAL COURSE OF EARLY AXIAL SPONDYLOARTHRITIS OVER TEN YEARS: LONG-TERM RESULTS FROM THE GERMAN SPONDYLOARTHRITIS INCEPTION COHORT. (2nd June 2020) - Poddubnyy, D.; Rios Rodriguez, V.; Torgutalp, M.; Verba, M.; Callhoff, J.; Protopopov, M.; Proft, F.; Rademacher, J.; Haibel, H.; Sieper, J.; Rudwaleit, M.
Abstract : Background: Previous studies showed that patients with non-radiographic and radiographic axial spondyloarthritis (nr- and r-axSpA) have similar disease burden and similar response to anti-inflammatory therapy given similar level of inflammatory activity. Only little is known, however, about long-term disease course in patients with early axSpA. Objectives: To investigate the long-term (up to 10 years) clinical course of patients with early axSpA. Methods: In total, 525 patients with early axSpA (r-axSpA with symptom duration ≤10 years and nr-axSpA with symptom duration ≤5 years) from the German Spondyloarthritis Inception Cohort (GESPIC) were included. The final patient classification was based on central reading results in 458 patients with available pelvic X-rays, and on local rheumatologist judgement in 67 patients. A total of 251 patients were finally classified as r-axSpA and 274 as nr-axSpA. Clinical evaluation, which included disease activity (BASDAI, C-reactive protein – CRP, ASDAS) as well as therapy recording, was performed at baseline and every 6 months thereafter until year 2 and annually thereafter till year 10. Treatment was conducted at the discretion of the local rheumatologist. Results: Since the cohort has started prior to introduction of TNF inhibitors (TNFi), only 2% patients received TNFi at baseline that increased to 23% at year 10 (15% in nr-axSpA and 31% in r-axSpA) – Figure 1 . The use of NSAIDs and csDMARDs decreased in both groups (Figure 1 ), while use of systemic steroids did not change substantially (9% at baseline, 8% at year 10). The proportion of patients with low disease activity according to BASDAI (<4) was higher in r-axSpA as compared to nr-axSpA at almost all time points, while the proportion of patients with low disease activity according to ASDAS (<2.1), as well as with ASDAS inactive disease (<1.3) was similar between nr-axSpA and r-axSpA (Figure 2 ). In the group of patients who completed year 10 (n=134 in total, 68 with nr-axSpA, 67 with r-axSpA) the same trends in therapy and disease activity were observed. Conclusion: Patients with nr-axSpA and r-axSpA showed a similar disease course in terms of disease activity on the group level. The drop-out rate in this observational cohort was overall high, but comparable between groups. The lower proportion of patients with nr-axSpA being treated with TNFi might reflect a later introduction of TNFi for this indication. Acknowledgments: GESPIC has been financially supported by the German Federal Ministry of Education and Research as well as by Abbott, Amgen, Centocor, Schering–Plough, and Wyeth. From 2010 till 2019 GESPIC has been supported by Abbvie. Disclosure of Interests: Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Valeria Rios Rodriguez Consultant of: Abbvie, Novartis, Murat Torgutalp: None declared, Maryna Verba: None declared, Johanna Callhoff: None declared, Mikhail Protopopov Consultant of: Novartis, Fabian Proft Grant/research support from: Novartis Pharma GmbH, Consultant of: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Judith Rademacher: None declared, Hildrun Haibel Consultant of: Abbvie, Jansen, MSD, and Novartis, Speakers bureau: Abbvie, Jansen, MSD, and Novartis, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Martin Rudwaleit Consultant of: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma